Comparative analysis of soybean transcriptional profiles reveals defense mechanisms involved in resistance against Diaporthe caulivora - Eilyn Mena; Guillermo Reboledo; Silvina Stewart; Marcos Montesano; Inés Ponce de León (Scientific Reports, 2023)
Abstract Soybean stem canker (SSC) caused by the fungal pathogen Diaporthe caulivora is an important disease affecting soybean production worldwide. However, limited information related to the molecular mechanisms underlying soybean resistance to Diaporthe species is available. In the present work, we analyzed the defense responses to D. caulivora in the soybean genotypes Williams and Génesis 5601. The results showed that compared to Williams, Génesis 5601 is more resistant to fungal infection evidenced by significantly smaller lesion length, reduced disease severity and pathogen biomass. Transcriptional profiling was performed in untreated plants and in D. caulivora-inoculated and control-treated tissues at 8 and 48 h post inoculation (hpi). In total, 2.322 and 1.855 genes were differentially expressed in Génesis 5601 and Williams, respectively. Interestingly, Génesis 5601 exhibited a significantly higher number of upregulated genes compared to Williams at 8 hpi, 1.028 versus 434 genes. Resistance to D. caulivora was associated with defense activation through transcriptional reprogramming mediating perception of the pathogen by receptors, biosynthesis of phenylpropanoids, hormone signaling, small heat shock proteins and pathogenesis related (PR) genes. These findings provide novel insights into soybean defense mechanisms leading to host resistance against D. caulivora, and generate a foundation for the development of resistant SSC varieties within soybean breeding programs.